Customers Attitude towards Wireless Internet Services in Bangladesh: An Empirical Study Comparing WIMAX Based and EDGE/EVDO Based Internet Service - Islam, SM Monirul; Ahamed, Bulbul (Journal of Business and Technology (Dhaka), 2012)
This study is an attempt to measure the attitude of customers towards the wireless Internet services in Bangladesh based on the Mertin Fishbein’s multi attribute attitude model. Some salient attributes (i.e., speed, bandwidth fluctuation rate) of WIMAX based and EDGE/EVDO based Internet services that affect the attitude of the customers have been selected which customers emphasizes to take purchase-decision as well as usage continuation decision. Two types of wireless Internet service providers (WIMAX and EDGE/EVDO) and ten salient attributes have been considered for this study. It has been found from the study that customers form more positive attitude towards WIMAX based Internet service than EDGE/EVDO based service. Observed differences in mean attitude of different attributes for the two categories of wireless Internet services are measured through Z-test to test the significance of those differences. Findings of this study may be used as an index by the Internet service providers for improvement of their services to satisfy the customers. Key words: Wireless Internet; Customer Attitude; WIMAX; EDGE; EVDO DOI: http://dx.doi.org/10.3329/jbt.v6i1.9994 Journal of Technology (Dhaka) Vol. 6(1), January-June, 2011 49-60